The Effect Of Human Resource Quality And Organizational Culture on Employee Performance in Work Motivation Moderation, in Bank Indonesia Representative Office Pematangsiantar - Azhar Syah; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
This study focuses on assessing how the quality of human resources and organizational culture influence employee performance, with work motivation as a moderating factor, at the Bank Indonesia Representative Office located in Pematangsiantar. A quantitative methodology was used, and data were analyzed using Structural Equation Modeling (SEM) using SmartPLS 3.0. Employees were selected as part of the research sample through purposive sampling based on certain criteria. The analysis results indicate that both Human Resource Quality and Organizational Culture positively and significantly influence Employee Performance. Furthermore, Work Motivation was also found to positively and significantly influence Employee Performance. It has been shown that Work Motivation enhances the influence of Organizational Culture on Employee Performance, although it does not significantly moderate the relationship between Human Resource Quality and Employee Performance. These results highlight the importance of effective human resource management, fostering a positive organizational culture, and enhancing work motivation to improve employee performance at Bank Indonesia in Pematangsiantar.